DESIMINASI TEKNOLOGI FERMENTASI PAKAN TERNAK (JERAMI) DENGAN PROBIOTIK UNTUK MENINGKATKAN PRODUKSI SAPI POTONG BAGI KELOMPOK TERNAK DESA ALUE IE PUTEH - Fitriani Fitriani; Zulfan Arico; Yulina Ismida; Fazrina Saumi; Juliati Juliati (LPPM dan PM Universitas Samudra, 2020)
Cows are one of the livestock that produce meat, milk, labor and others. But lately the productivity of cattle has decreased due to changes in land and climate function and maintenance patterns that are still traditional in nature so that the intake of feed needs is not met both in quality and quantity. The purpose of this activity is to enhance the role and function of universities, BUMK, and livestock groups in accelerating and expanding adoption of livestock innovations to support livestock development through partnerships, government and private institutions. Providing training for livestock groups on the manufacture of probiotics and about the application of biotechnology for animal feed fermentation (straw) with probiotics to increase beef cattle production. Approach method is done by lecture method and field practice. Based on the results of the activity, it was found that the high level of participation of partners in the community service program the application of fermentation technology had a positive impact on the implementation of the service activities program (PKM). The implementation of the program is able to produce products that can improve beef cattle productivity so that it can improve the economy of the Alue Ie Puteh community, especially livestock farmers.